5-ALA-Induced Fluorescent Urine Cytology in Comparison with Conventional Cytology, BTA-TRAK, and NMP-22 Tests in the Diagnosis of Bladder Cancer - Nerli, Rajendra B; Rangrez, Shadab; Ghagane, Shridhar C.; Lalakia, Parth; Chandra, Shoubhik; Chandra, Shreya (Brazilian Journal of Oncology, 2025)
Introduction To assess the sensitivity fluorescent urine cytology induced by 5-aminolevulinic acid (5-ALA) in the diagnosis of bladder cancer and to compare the sensitivity and specificity with currently available markers approved by the United States Food and Drug Administration (FDA), bladder tumour antigen (BTA-TRAK, Bard Diagnostic Sciences, Redmond, WA, United States) assay based on enzyme-linked immunosorbent assay (ELISA), nuclear matrix protein 22 (NMP-22), and conventional cytology.Materials and Methods Age- and gender-matched patients ≥ 18 years of age admitted with imaging-confirmed bladder cancer and non-malignant conditions formed the cases and controls respectively. A freshly-collected voided urine sample was divided into four parts, with each part used to perform: a) conventional cytology with Papanicolaou staining; b) the BTA-TRAK assay; c) the NMP-22 assay; and d) 5-ALA-induced fluorescent urine cytology. The resected bladder specimen was sent for histopathological examination.Results In low-grade bladder cancers, the sensitivity of 5-ALA fluorescent cytology was of 88.02%, which was significantly higher than conventional cytology (p < 0.0001), the NMP-22 assay (p < 0.0035), and the BTA-TRAK assay (p < 0.0007). The sensitivity of 5-ALA fluorescent cytology was significantly higher in high-grade lesions when compared to conventional cytology (p < 0.0005) and the BTA-TRAK assay (p < 0.039).Conclusions Fluorescent urine cytology induced by 5-aminolevulinic acid is a highly-sensitive test in the diagnosis of bladder cancer, and its sensitivity rates are significantly superior to those of conventional cytology, the NMP-22 assay, and the BTA-TRAK assay.
Keywords: bladder cancer; cytology; urothelial carcinoma; 5-aminolevulinic acid; sensitivity; specificity